Independent Learning-Independent Campus Curriculum: Students’ Reflection on EFL Quality in English Education - Fahriany Fahriany; Viviana Lisma Lestari; Hasnan Yasin (STAI Hubbulwathan Duri, 2023)
In the current information age, English as a foreign language (EFL) education at higher education institutions must provide students with more than just proficiency in English. However, Developing a curriculum that addresses these issues at the college level is a complex process that has gained universal attention in higher education institutions across Indonesia, driven by the influence of globalization trends and advancements in information technology. The aim of this study was to examine the application of to improve the quality of EFL education in the English Education Department at the Faculty of Educational Sciences, Syarif Hidayatullah State Islamic University. A descriptive qualitative approach was employed, using a questionnaire and interviews to collect data from 61 students in the English Education Program. The findings of this study indicate that while most students are aware of the Independent Learning-Independent Campus Program, there has been a lack of introduction and implementation of the program in the Department of English Language Education. However, students are still attracted to the program due to their perception of its significance and its potential benefits for their studies and future careers. They believe that participating in the program will not only provide them with new knowledge and experiences but also develop skills that are valuable for their profiles and prospective careers, such as communication, teamwork, leadership, and other essential skills.